Asymptotical analysis of generalized Hirota–Satsuma type system - Kriauzienė, Rima; Krylovas, Aleksandras (Lietuvos matematikos rinkinys, 2010)
Paper deals with the nonlinear coupled equations of the well known in the literature Hirota–Satsuma type system. The asymptotic analysis of this system, which is based on the principle of two scales and on averaging of weakly nonlinear hyperbolic systems along characteristics is presented in the paper. The asymptotic analysis shown that the system disintegrates on three independent Korteweg–de Vries equations in the non-resonance case, and the system describes an interaction of periodical nonlinear waves in the resonance case.